Transparansi Anggaran dan Akuntabilitas Pemerintah: Analisis Peran Manajemen Keuangan Sektor Publik di Era Digital - Yani Padila Padila; Muhammad Budi Utama; Sinardi (Bussiness Academy of Lombok, 2026)
This study aims to analyze the role of public sector financial management in enhancing government budget transparency and accountability in the digital era. The research objectives include examining how digital tools such as cloud-based financial systems, big data analytics, and e-budgeting applications contribute to better fiscal oversight and public trust. The methodology employed is a qualitative descriptive analysis combined with case studies from selected countries, drawing on secondary data from government reports, academic literature, and international databases. Key findings reveal that effective financial management in the digital age significantly reduces corruption risks and fosters citizen participation through real-time data access. However, challenges such as digital divides and data security vulnerabilities hinder full implementation. The discussion highlights the need for adaptive policies to integrate technology with traditional accountability mechanisms, ultimately promoting sustainable governance. This research contributes to the field of public administration by providing insights for policymakers on leveraging digital innovations for fiscal transparency.